Strategic Supply Chain Framework as an Effective Approach to Procurement of Public Construction Projects in Nigeria - Dim, N.U; Ezeabasili, A.C.C (International Journal of Management and Sustainability, 2015)
A lot of abandoned construction projects, and failed projects in the Nigerian construction industry due to the ignorance to adopt and implement modern procurement strategy prompt this research work. A survey was conducted on 38 procurement practitioners at the Federal Ministry of Housing, Land and Urban Development, Major contractors, and Tier suppliers. The result from the survey showed that 78% of respondents confirmed that the current Nigerian public procurement system is less effective towards achieving an improved construction performance and the successful delivering of construction projects. More so, 22% of respondents argued that the Nigerian current procurement system is effective to achieve an improved construction performance if properly practiced in accordance with the Nigerian procurement act (2007). However, 74% of respondents believed that the strategic supply chain framework, as an approach to public procurement in Nigeria, will be more effective towards successful delivering of construction projects, and achieving improved construction performance. Also, the result from the three interviews conducted during this research showed that the reasons for the poor Nigerian current procurement system is attributed to poor pre-tendering and tendering processes, poor supply chain integration and management, Political interference and inference, and the corruption amongst the procurement stakeholders.